The Effect of Government Debt, External Debt and their Interaction on OECD Interest Rates - Turner, David (OECD Economics Department Working Papers, 2013)
In the wake of the financial crisis there has been renewed focus on the importance of a country's net external debt position in determining domestic interest rates and, relatedly, its vulnerability to a crisis. This paper extends the panel estimation of OECD countries described in Turner and Spinelli (2012) to investigate the effect of external debt and its interaction with government debt on the interest-rate-growth differential. The inclusion of net external debt is found to be significant in both economic and statistical terms, and of particular importance for euro area countries in the post-crisis period. The results imply that the interest-rate effect of marginal increases in external debt or government debt is non-linear and dependent on the initial levels of debt, with the interest rate effect rising sharply in the post-crisis period for euro area countries which have a combination of both high external debt and high government debt. The policy implications for those countries under financial market pressure, especially within the euro area, are that reducing external deficits and debt are at least as important as reducing government deficits and debt. In any case, the effect of higher net external debt on interest rates provides a feedback effect which may prevent countries running sustained large current account imbalances over a long period. However, evidence of an asymmetry in the effect (between the effect of net external debt and net external assets) suggests that the pressure for adjustment will apply more strongly to deficit countries. It also implies that increased polarisation of external debt positions will raise the overall level of global interest rates